German inbound investment, corporate tax planning, and thin-capitalization rules: a difference-in-differences approach - Michael Overesch; Georg Wamser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper investigates tax planning behavior by means of inter-company finance and the effectiveness of fighting back via thin-capitalization rules. A simple theoretical model, which considers the financing decision of a multinational company, is used to obtain empirical implications. The empirical analysis, based on German inbound investment data from 1996 until 2004, supports a significant impact of tax rate differences on the use of intra-company debt. The effectiveness of the German thin-capitalization rule is tested by using legal amendments as natural experiments. The results suggest that the German thin-capitalization rule induces significantly lower intra-firm debt-levels of inbound investments. Hence, tax planning via intra-firm finance is effectively limited.
Keywords: H26; H25; G32; 330; Corporate Income Tax; Multinationals; Thin-Capitalization Rule; Difference-in-Differences; Firm-Level Data